(untitled) (Research, Society and Development, 2025)
Iron deficiency anemia is the most prevalent nutritional disorder worldwide and results from insufficient iron availability, an essential mineral for erythropoiesis and hemoglobin synthesis. It is classified as a microcytic and hypochromic anemia, presenting clinically with fatigue, pallor, and reduced functional capacity. This study aimed to synthesize recent evidence on the pathophysiology of iron deficiency anemia, the main hematological parameters involved in its diagnosis, and general preventive considerations. A narrative literature review was conducted in PubMed/MEDLINE, SciELO, LILACS, and Google Scholar databases, using Portuguese and English descriptors related to iron deficiency anemia and hematological alterations. Articles published in the last five years addressing physiopathological mechanisms, laboratory indicators, and general aspects of prevention were included. The reviewed literature indicates that iron deficiency progresses gradually, beginning with decreased ferritin levels, followed by reduced serum iron, microcytosis, hypochromia, and decreased hemoglobin. The complete blood count remains fundamental, with MCV, MCH, MCHC, and RDW highlighted as key markers for the identification of erythrocyte alterations. It is concluded that integrating hematological parameters with an understanding of the underlying physiology is essential for the proper identification of iron deficiency anemia and the implementation of preventive strategies.